(untitled) (Revista Contexto & Educação, 2026)
Bullying is widely recognized as a serious psychosocial issue that affects students’ health and development. Two studies were conducted with the following objectives: 1) integrating available evidence in the literature on how sociometric status related to boys’ perpetration of school bullying, and 2) identifying sociometric positions of a group of boys identified as aggressors in classrooms. The cross-sectional study involved 165 male adolescents aged 11 to 19. Data was collected using the Sociometric Scale and analyzed descriptively and exploratively. The results revealed various factors influencing the relationship between sociometric status and bullying. Despite both aggressors and victims facing similar levels of rejection, perceptions varied, with victims seen as more vulnerable and aggressors as stronger. The complexity of popularity dynamics and associated contradictions highlighted the interconnectedness of sociometric status, rejection, and popularity in the context of bullying. The findings also suggested that aggressors were perceived as disruptive by peers, showing prevalence in behaviors associated with rejection and disorder. Both studies provided significant insights into bullying dynamics among boys, its link with sociometric status, and the complexities of social interactions in classrooms. The theoretical and practical implications are extensive. It highlighted the intricate nature of social interactions and sociometric status, emphasizing their influence on bullying dynamics. This underscores the need to further understand how rejection, popularity, and perceptions impact students’ aggressive behaviors. Moreover, identifying aggressors as disruptive by peers indicates the importance of intervention strategies focusing on this behavior.